Utilization of Macadamia Nutshell Residue for the Synthesis of Magnetic Activated Carbon toward Zinc (II) Ion Removal - Minh-Trung Dao; Thi-Phuong-Linh Tran; Duc-Thuong Vo; Van-Kieu Nguyen; Le-Thuy-Thuy-Trang Hoang (Advances in Materials Science and Engineering)
In this study, macadamia nutshell residue, a prevalent leftover and green agricultural waste in Vietnam, was utilized to prepare a magnetic activated carbon adsorbent. The obtained material was characterized by its surface functionalities, elemental composition, crystalline structure, and magnetic properties. The characterization results revealed that the composite comprised Fe3O4 nanoparticles attached to the carbon matrix. The saturation magnetization (Ms) of the composite was found to be 38.2 emu g−1, indicating a convenient separation of the solid adsorbent from aqueous media using an external magnetic field. The feasibility of removing zinc (II) ion from an aqueous solution of the activated carbon/Fe3O4 (AC/Fe3O4) composite was examined. The adsorption kinetics were best explained by the Elovich model and the pseudo-second-order model. The adsorption capacity at equilibrium and the initial rate of Zn2+ adsorption determined by the pseudo-second-order model were 22.73 mg g−1 and 4.18 mg g−1 min−1, respectively. The implications of this study are that a low-cost, green, and magnetically separable material prepared by a large-scale available solid waste can be a promising adsorbent for the elimination of heavy metals.